2010
DOI: 10.1097/wco.0b013e32833735cf
|View full text |Cite
|
Sign up to set email alerts
|

Neurosteroids and epilepsy

Abstract: Purpose of review-Neurosteroids are a family of compounds synthesized directly in the brain by transforming cholesterol into pregnenolone, which is then converted to compounds such as allopregnanolone and allotetrahydrodeoxycorticosterone. In view of their ability to modulate neurotransmission, neurosteroids may influence the clinical course of epileptic disorders. In this review, we highlight two emerging properties of neurosteroids, that is, their anticonvulsant and antiepileptogenic activities.Recent findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 41 publications
0
65
0
1
Order By: Relevance
“…Recent studies suggest that neurosteroids play a role in epileptogenesis (Edwards et al, 2001; Biagini et al, 2006; 2009a; 2010; Reddy et al, 2010; Reddy, 2013a). Using the kindling model, we demonstrated that the development and persistence of limbic epileptogenesis are impaired in mice lacking progesterone receptors (Reddy and Mohan, 2011).…”
Section: Anticonvulsant and Antiepileptogenic Activity Of Neurosteroidsmentioning
confidence: 99%
“…Recent studies suggest that neurosteroids play a role in epileptogenesis (Edwards et al, 2001; Biagini et al, 2006; 2009a; 2010; Reddy et al, 2010; Reddy, 2013a). Using the kindling model, we demonstrated that the development and persistence of limbic epileptogenesis are impaired in mice lacking progesterone receptors (Reddy and Mohan, 2011).…”
Section: Anticonvulsant and Antiepileptogenic Activity Of Neurosteroidsmentioning
confidence: 99%
“…Natural neurosteroids such as allopregnanolone are not orally active, but one new synthetic neurosteroid, ganaxolone, the 3 ␤ -methyl analogue of allopregnanolone, is orally active, lacks hormonal side effects, and has entered phase II clinical trials for infantile spasms, partial seizures, and catamenial epilepsy [Reddy, 2010]. A neuroactive steroid like ganaxolone may be useful in the treatment of anxiety and seizures associated with FXS, and has advantages over benzodiazepines, given the low occurrence of side effects and evidence of preferential effects at extrasynaptic, tonically active ␦ -subunit-containing receptors [Biagini et al, 2010;Mihalek et al, 1999;Reddy, 2010].…”
Section: Gabaergic System Components As Potential Therapeutic Targetsmentioning
confidence: 99%
“…Several observations support this notion. In the pilocarpine model, rats develop seizures after a latent period that mirrors that of P450scc elevation, and treatment with finasteride (a neurosteroid synthesis inhibitor) is capable of reducing latency-to-seizure expression after SE, as well as exacerbating seizure intensity [215]. …”
Section: Neurosteroids As Potential Endogenous Antiepileptogenic mentioning
confidence: 99%